Carrier injection efficiency in III-nitride light emitting diodes: Effective potential correction - Witzigmann, Bernd; Romer, Friedhard (Optics InfoBase Conference Papers, 2020)
A model for carrier injection efficiency of III-nitride based light emitters with multiple quantum wells is described. With a combination of semi-classical and quantum transport, it matches a wide range of experimental LED data for solid-state lighting.
CRIS-Team Scopus Importer:2021-06-11